Secretory cargo sorting by Ca(2+)-dependent Cab45 oligomerization at the trans-Golgi network - Crevenna, Alvaro H. (J Cell Biol, 2016)
Sorting and export of transmembrane cargoes and lysosomal hydrolases at the trans-Golgi network (TGN) are well understood. However, elucidation of the mechanism by which secretory cargoes are segregated for their release into the extracellular space remains a challenge. We have previously demonstrated that, in a reaction that requires Ca(2+), the soluble TGN-resident protein Cab45 is necessary for the sorting of secretory cargoes at the TGN. Here, we report that Cab45 reversibly assembles into oligomers in the presence of Ca(2+). These Cab45 oligomers specifically bind secretory proteins, such as COMP and LyzC, in a Ca(2+)-dependent manner in vitro. In intact cells, mutation of the Ca(2+)-binding sites in Cab45 impairs oligomerization, as well as COMP and LyzC sorting. Superresolution microscopy revealed that Cab45 colocalizes with secretory proteins and the TGN Ca(2+) pump (SPCA1) in specific TGN microdomains. These findings reveal that Ca(2+)-dependent changes in Cab45 mediate sorting of specific cargo molecules at the TGN.